Comparison of different gutta-percha root filling techniques: Thermafil, Quick-Fill, System B, and lateral condensation - (:unkn) unknown (MOSBY, INC, 2002)
Objectives. In this in vitro study, the core (gutta-percha or gutta-percha and carrier)/sealer ratio and the sealing ability were calculated for 4 different gutta-percha techniques: Thermafil, JS Quick-Fill, System B, and lateral condensation. Study design. One hundred single-rooted teeth were instrumented and obturated. Forty of the teeth were embedded in resin and sectioned horizontally at 1, 2,3, arid 4 mm from the anatomic apex. Photographs were taken of each section, and the total area of the canal filled with core material or sealer was calculated. Sixty of the teeth were kept in wet storage for 90 days, after which the teeth were immersed in 2% methylene blue for 48 hours. The length of dye penetration was measured. Results. Roots obturated with Thermafil and JS Quick-Fill contained significantly more core material than did those obturated with System B or with lateral condensation. The lateral condensation technique had the lowest core/sealer ratio (P < .05). Roots using Thermafil and Quick-Fill showed significantly less dye leakage than did the lateral condensation technique. Conclusions. Through use of these techniques in vitro, Thermafil and JS Quick-Fill with carrier and System B were found to be superior to the lateral condensation technique in terms of core/sealer ratio. Thermafil and Quick-Fill were superior to lateral condensation in terms of dye leakage.
Keywords: OBTURATION TECHNIQUES; SMEAR LAYER; ABSENCE; ADAPTATION